Prevalence And Predictors Of Post-acute Covid Syndrome Among Infected Healthcare Workers at University Malaya Medical Centre - Say Hiang Lim; Yin Cheng Lim; Rafdzah Ahmad Zaki; Bushra Megat Johari; Chung Yuan Chang; Sharifah Faridah Syed Omar; Amirah Azzeri; Maznah Dahlui; Adeeba Kamarulzaman (Plos One, 2024)
Indexed by WOS/Scopus/ERA